2018
DOI: 10.1194/jlr.m080465
|View full text |Cite
|
Sign up to set email alerts
|

Lipid imaging for visualizing cilastatin amelioration of cisplatin-induced nephrotoxicity

Abstract: Nephrotoxicity is a major limitation to cisplatin antitumor therapies. Cilastatin, an inhibitor of renal dehydropeptidase-I, was recently proposed as a promising nephroprotector against cisplatin toxicity, preventing apoptotic cell death. In this work, cilastatin nephroprotection was further investigated in a rat model, with a focus on its effect on 76 renal lipids altered by cisplatin, including 13 new cisplatin-altered mitochondrial cardiolipin species. Lipid imaging was performed with MALDI mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 69 publications
(72 reference statements)
2
19
0
Order By: Relevance
“…Interestingly, for cilastatin-induced kidney toxicity in an animal model, lipid imaging was performed by MALDI mass spectrometry of kidney sections. In the study, statin therapy successfully lowered the lipid distribution, which had previously been induced by cisplatin toxicity, and decreased the lipid peroxidation capacity, with statin showing no effect on the lipid distribution in the normal control [ 49 ]. This paper described a new link in the pathology between AKI and the lipid distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, for cilastatin-induced kidney toxicity in an animal model, lipid imaging was performed by MALDI mass spectrometry of kidney sections. In the study, statin therapy successfully lowered the lipid distribution, which had previously been induced by cisplatin toxicity, and decreased the lipid peroxidation capacity, with statin showing no effect on the lipid distribution in the normal control [ 49 ]. This paper described a new link in the pathology between AKI and the lipid distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the protective properties of myricetin are speculated to be linked with mitigating oxidative and inflammatory response in the colon of experimental animals. Cisplatin administration creates hydroxyl radical (•OH), superoxide anion (O2•−), and hydrogen peroxide (H 2 O 2 ), which play a crucial role in the instigation of lipid peroxidation [59]. Chang et al (2002) [60] reported that cisplatin treatment initiates an autocatalytic lipid peroxidation reaction that amplifies the levels of fatty acids in the mucosal layer of the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…MSI lipidomics has extensively been performed on rodent material by matrix-assisted laser desorption/ionization (MALDI), the mainstream method for MSI, which is characterized by the addition of an organic chemical matrix on biological specimens. This technology has been used on normal tissue [19,20,21,22,23] and in different pathophysiologic contexts, such as acute renal injury [24], diabetes/obesity [25], renal acidosis [26] polycystic kidney [27], drug-induced nephrotoxicity [28,29], bisphenol toxicity [30], polymyxin toxicity [31], Fabry disease [32,33], and in glomerulopathies, such as diabetic nephropathy [34] and IgA nephropathy [35].…”
Section: Lipid Imaging Of the Kidney: Maldi-msimentioning
confidence: 99%